Discitis following urinary tract infection manifesting as recurrent autonomic dysreflexia related to truncal movements in a person with tetraplegia. Issue 12 (17th December 2020) - Subramanian, Vaidyanathan; Hughes, Peter; Soni, Bakul; Oo, Tun
Abstract : A 44-year-old male person with tetraplegia (C-5 AIS—A (American Spinal Cord Injury Association Standard Neurological Classification of Spinal Cord Injury Impairment Scale)) developed urinary tract infection and received appropriate antibiotic. Subsequently, he started sweating and shivering when he was sitting up; these symptoms resolved while lying on his back. Autonomic dysreflexia triggered by truncal movements continued to occur for 3 months. CT of the spine showed L5–S1 discitis. MRI of the spine showed diffuse marrow oedema in L5 and S1 vertebrae and a large abscess at L5/S1 level. Blood culture yielded Serratia marcescens sensitive to meropenem. Meropenem followed by ertapenem was given for 12 weeks. After 11 months, MRI showed resolution of discitis and epidural collection. The patient was able to sit up for 9 hours without developing autonomic dysreflexia. If a person with cervical spinal cord injury develops posture-related autonomic dysreflexia (eg, in sitting position, lying on sides or while hoisted), disco-vertebral pathology should be suspected.